COLD CONSERVATION OF EGGS FROM Sitotroga cerealella (Olivier) IN REFRIGERATION AND VACUUM PACKAGED AT DIFFERENT PRESSURES - RAMOS, JANETH PATRICIA; JIMÉNEZ-V., JADES (Revista Colombiana de Entomología, 1993)
A work on the shill conservation of Sitotroga cerealella (Oliver) eggs using vacuum packing and refrigeration under different pressures, was done at the Plant Protection Laboratory at ICA's Experiments Station and at the Perkins Biological Products Laboratory, both located at Palmira (Valle, Colombia). Five .storage periods (20, 30, 40, 50, and 60 days) and three vacuum pressures (0, 5 y 10 PSI) were used as treatments, in a complete randomized blocks design with three repetitions. The mean environmental conditions during the study period at Palmira were: Temperature: 23. 61°C; Relative Humidity: 76.75%. The storing conditions in the refrigerator were: Temperature: 7.15°C; Relative Humidity: 78.57%. Best results were obtained by using a vacuum pressure of 10 PSI and up to 35 days of the storage period, when the number of parasitized eggs per square inch was equal to 2400, the mínimum number required by ICA, according to the Resolution number 20 of January 5th, 1990. The next effective treatment was the vacuum pressure of 5 PSI with 28 d.y. Jf storage period. With the non-vacuum treatment (0 PSI), a storage period up to 25 days was efficient to fit the required mínimum of 2400 parasitized eggs. It is suggested to vacuum store the eggs of S. cerealella to attain an increase in the usable period.